ATYPICAL PRESENTATION OF METASTATIC LOBULAR BREAST NEOPLASM - MADHURIMA BHATTACHARYYA; PRASIT KUMAR GHOSH; UTPAL GOSWAMI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
The diagnosis of cholecystitis is based on physical examination, laboratory tests, and abdominal ultrasound. After cholecystectomy, the surgical specimen is sent to the pathology department for routine histopathological examination to rule out pre-malignant and malignant conditions. Even less common is metastatic breast cancer that has spread to the gallbladder, which is itself a rare occurrence. We present a case of a 55-year-old female patient who underwent cholecystectomy for symptomatic chronic calculous cholecystitis. On histological examination, to the utmost surprise, a metastatic deposit in the wall of the gallbladder was detected by the pathologist, with a specific pattern of cell disposition, pointing to the primary site to be the breast, of which the patient was totally unaware. Metastasis in the gallbladder from primary lobular carcinoma of the breast was confirmed by a Tru-Cut biopsy from an ill-defined right breast lesion, with immunohistochemistry showing positive E-cadherin staining. Symptoms of right hypochondrial pain with nausea and vomiting in a patient should be investigated meticulously, as it can ultimately lead to the diagnosis of primary breast cancer. The role of the pathologist is emphasized in tracing the primary source of cancer and arriving at a clinical diagnosis.